Influencing Factors Related to Female Sports Participation Under the Implementation of Chinese Government Interventions: An Analysis Based on the China Family Panel Studies - Fang, Ping; Sun, Lei; Shi, Shu Sheng; Ahmed Laar, Rizwan; Lu, Yan (Frontiers in Public Health, 2022)
Objectives: Regular participation in physical activity (PA) is a gendered phenomenon in China. The purpose of our research is to identify influencing factors of women PA time. Study design：This study is a cross-sectional study. Methods: Data were collected from the nationally reprehensively China Family Panel Studies (CFPS) database (2018) to analyze the personal information, family background and lifestyle and health on women PA time. Multiple classification logistic regression was used to quantify the association between independent variables and PA time. Results: 1) The women aged 30-39, western and central areas, low educated, rural, married, low income, overweight and obese and good and normal appearance, and having children and family population more than 3 have no or 90 minutes time for PA. When less than 3 hours a day for internet use, moderate sleep time, healthy body and without chronic diseases give women 180 minutes for PA, and more than ¥500 medical expenditures have no time for PA. Women with overweight and obesity have a higher probability of not participating in PA. Women with lower appearance ratings spent more time for PA participating. Conclusions: 1) High income and education, unmarried, western urban women have time for PA participation, and limited by children and family sizes. 2) Women with health body, no chronic diseases and no medical expenses, and moderate sleep and appropriates internet use time give women more time for PA participation.